PENGARUH GADGET TERHADAP TUMBUH KEMBANG ANAK SISWA KELAS 4 – 6 DI SDN 213 LAPONGKODA KECAMATAN TEMPE KABUPATEN WAJO - Syamsuddin; Tetti Surianti; Hasnidar; Ruslang (Jurnal Ilmiah Mappadising, 2020)
The prevalence of the influence of gadgets increases in line with changes in the growth and development of elementary school age children. Excessive use of gadgets causes children's growth and development to be less than optimal. The purpose of this research is to determine the effect of gadgets on the growth and development of children at SDN 213 Lapongkoda, Tempe District, Wajo Regency. This type of research is quantitative research using a Cross Sectional approach. The population in this study were all students in grades 4-6 at SDN 213 Lapongkoda, totaling 268 students. Sampling technique using purposive sampling totaling 73 students. Data were collected through a questionnaire. The analysis test used a computer program, namely SPSS 22 to assess frequency statistical data and the Chi-Square Test on the Fisher Exact Test on bivariate variables, the value of Exact sing was obtained. (2-sided) on the variable, the use of gadgets was obtained a value of (p) = 0.022 which means <0.05 value so it can be concluded that there is a significant influence on the growth and development of children on these variables. The conclusion of the researcher recommends the importance of supervising and limiting excessive use of gadgets in children so that children's growth and development can be optimal. This is because gadgets not only have a positive influence, but also have a negative influence on children's growth and development. Abstrak Prevalensi pengaruh gadget meningkat sejalan dengan perubahan pada tumbuh kembang anak usia sekolah dasar. Penggunaan gadget secara berlebihan menyebabkan tumbuh kembang anak menjadi kurang optimal. Tujuan peneilitian ini mengetahui pengaruh gadget terhadap tumbuh kembang anak di SDN 213 Lapongkoda Kecamatan Tempe Kabupaten Wajo. Jenis penelitian yaitu peneltian kuantitatif dengan menggunakan pendekatan Cross Sectional. Populasi dalam penelitian ini semua anak siswa kelas 4 – 6 di SDN 213 Lapongkoda yang berjumlah 268 Siswa. Teknik Pengambilan Sampel menggunakan pusposive sampling berjumlah 73 siswa. Data dikumpulkan melalui kuesioner. Uji analisis menggunakan program komputer yaitu SPSS 22 untuk menilai data statistik frekuensi dan Uji Chi – Square pada Fisher Exact Test pada variabel bivariat diperoleh nilai Exact sing.(2-sided) pada variabel, penggunaan gadget yaitu diperoleh nilai (p) = 0,022 berarti α < 0,05 nilai sehingga dapat disimpulkan bahwa ada pengaruh yang bermakna terhadap tumbuh kembang anak pada variabel tersebut. Kesimpulan peneliti menganjurkan akan pentingya mengawasi dan membatasi penggunaan gadget secara berlebihan pada anak sehingga tumbuh kembang anak dapat menjadi optimal. Hal ini dikarenakan gadget bukan hanya memiliki pengaruh positif, namun juga memiliki pengaruh negatif terhadap tumbuh kembang anak.